Sustainability and Environmental Impact of Ethanol and Oxyhydrogen Addition on Nanocoated Gasoline Engine. (20th January 2022) - Padmanabhan, Sambandam; Giridharan, K.; Stalin, Balasubramaniam; Elango, V.; Vairamuthu, J.; Sureshkumar, P.; Jule, Leta Tesfaye; Krishnaraj, Ramaswamy
Abstract : Climate change, clean air, renewable energy, nontoxic surroundings, and the opportunity to live in a healthy community are just few of the issues that environmental sustainability addresses. To improve environmental health and quality of life, several researchers have turned their attention to alternative energy sources like ethanol and oxyhydrogen. In latest years, significant progress has been made in the development of ethanol and hydrogen as clean energy sources. A higher octane rating is achieved by mixing ethanol with gasoline rather than using regular gasoline. A novel mix of oxyhydrogen, ethanol, and gasoline is ecologically friendly while simultaneously increasing the performance of gasoline engines. In this study, a nanoparticle-coated piston on a low heat rejection gasoline engine fuelled by an ethanol-gasoline mix with oxyhydrogen addition was investigated. It has been evaluated that thermal efficiency improved by up to 25% while fuel consumption can be reduced by up to 28% on a volume basis compared to the baseline engine. Furthermore, the decrease in harmful carbon monoxide reached around 10%, and the reduction in unburned hydrocarbon emissions reached 18%.